Inflammation and hemostatic system: a selection of involved clinical disorders - Francesco Marongiu; Antonella Mameli; Silvia Marongiu; Doris Barcellona (Bleeding, Thrombosis and Vascular Biology, 2026)
The role of the hemostatic system in host defense underscores the significant connection among coagulation, platelets, and inflammation. Both the hemostatic and the immune systems share a common ancestral origin. During infections, blood coagulation and platelet activation work in tandem with the immune system to combat bacterial and viral threats. Together, they help limit the spread of these pathogens by forming a fibrin clot network that not only kills pathogens but also promotes tissue repair. However, an excessive response is dangerous, as it can lead to both thrombosis and bleeding. The aim of this narrative review is to present the link between inflammation and the hemostatic system across different pathological conditions, such as infectious diseases (sepsis, plague, COVID-19 infection, Ebola, and Dengue virus infection, and malaria) and autoimmune diseases (antiphospholipid syndrome, systemic sclerosis, and rheumatoid arthritis). Although infectious diseases are characterized by a direct attack on the innate immune system, which in turn activates blood coagulation and platelets, Autoimmune diseases, through antibody production, can induce a coagulative reaction that can generate both thrombosis and fibrosis.